2012
DOI: 10.1186/1476-511x-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Study of lipid profile and parieto-temporal lipid peroxidation in AlCl3 mediated neurotoxicity. modulatory effect of fenugreek seeds

Abstract: BackgroundPeroxidation of lipid (LPO) membrane and cholesterol metabolism have been involved in the physiopathology of many diseases of aging brain. Therefore, this prospective animal study was carried firstly to find out the correlation between LPO in posterior brain and plasmatic cholesterol along with lipoprotein levels after chronic intoxication by aluminium chloride (AlCl3). Chronic aluminum-induced neurotoxicity has been in fact related to enhanced brain lipid peroxidation together with hypercholesterole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…It is likely that oxidative stress is one of the causes of astroglial dysfunction during Al intoxication 22 as evidenced here by TAS decrease and induced lipid peroxidation. 13 With regard to the effect of FSP supplementation, we have clearly demonstrated that the whole fenugreek seed had a compensating effect on IL-6 secretion towards AlCl 3 disrupting action in the brain. Different components of the plant endowed with anti-inflammatory and immunomodulating properties might be responsible for this effect.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is likely that oxidative stress is one of the causes of astroglial dysfunction during Al intoxication 22 as evidenced here by TAS decrease and induced lipid peroxidation. 13 With regard to the effect of FSP supplementation, we have clearly demonstrated that the whole fenugreek seed had a compensating effect on IL-6 secretion towards AlCl 3 disrupting action in the brain. Different components of the plant endowed with anti-inflammatory and immunomodulating properties might be responsible for this effect.…”
Section: Discussionmentioning
confidence: 94%
“…11,12 A previous study carried out by our laboratory has shown that after Al treatment, fenugreek seeds showed an anti-peroxidative effect in the posterior brain that was correlated to its antioxidant activity. 13 Relying on this preliminary result, as well as on the presumed anti-inflammatory property of this plant and the contribution of antioxidants in this phenomenon, we have chosen to investigate the neuroprotective effect of fenugreek seeds. …”
Section: Introductionmentioning
confidence: 99%
“…LDLB have less size (d 25.5-25.75) comparing to LDLA (d > 25.75) and are characterized by a lower content of polar lipids, as well as a higher content of cholesterol esters. Lipoproteins of this subfraction are slowly removed from the bloodstream that is caused by their low affinity to B/E-receptors for LDL, higher sensitivity to glycosylation and oxidative damage [31]; they also have a high affinity to scavenger-receptors of macrophages [32].…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental model of AlCl 3 -fed rats, simultaneous supplementation of fenugreek seeds powder or extract for 5 months enhanced the levels of LPO in posterior brain, liver and plasma, along with lactate dehydrogenase (LDH) activities, whereas total cholesterol, TG and LDL-cholesterol levels reversed, suggesting an antiperoxidative role in the brain which may be attributed to its modulatory effect on plasma lipid metabolism (Belaïd-Nouira et al, 2012).…”
Section: Antilipidemic Effect Of Trigonellamentioning
confidence: 99%